Pengaruh Celebrity Endorser, Brand Image dan Harga terhadap Minat Beli Konsumen pada Geprek Bensu Kawi Malang - Agustin Puji Lestari; Rusno Rusno; Iva Nurdiana Nurfarida (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This study aims to determine the effect of celebrity endorser, brand image and price on consumer buying interest in Geprek Bensu Kawi Malang. This research was conducted in Malang City and the population in this study were consumers who had bought and consumed food in Geprek Bensu Kawi Malang as many as 110 respondents. The sampling technique in this study used the accidental sampling method and the data obtained from the distribution of questionnaires to respondents, the test of the research instrument was carried out with validity and reliability tests. The data analysis technique used is multiple linear regression analysis using SPSS. The results showed that simultaneous celebrity endorser which has a significance value of 0,000 <0.05, brand image that has a significance value of 0.353> 0.05 and a price that has a significance value of 0,000 <0.05 has a significant effect on buying interest partial celebrity endorser has a significant effect on buying interest, brand image has no significant effect on buying interest and price has a significant effect on buying interest.